Magnetic Gradient Survey of the Marpole Period Dionisio Point (DgRv-003) Plankhouse Village, Northwest Coast of North America. (3rd September 2017) - Dolan, Patrick; Grier, Colin; Markussen, Christine; Simon, Katie
ABSTRACT: Architectural reconstructions of plankhouses are central to the study of household and community organization on the Northwest Coast of North America. However, the sample of substantially excavated houses is constrained by their size, stratigraphic complexity, and typically limited surface expression. We present the results of a magnetic gradiometry survey of the Dionisio Point site (DgRv-003) village, occupied ca.a.d. 500–700 on the coast of British Columbia, Canada. Survey of four house platforms reveals patterning of magnetic anomalies consistent with the structure of shed-roof houses, a design recorded ethnographically and identified archaeologically at the site. These results suggest a consistent pattern of spatial and, potentially, social organization of the households. The similarity of patterns suggests that magnetometry may be useful for guiding plankhouse excavations elsewhere on the Northwest Coast, providing a means for expanding our knowledge of houses without relying solely on traditional excavation methods.